2017
DOI: 10.1021/acs.jpca.7b08351
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of the Geometrical and Electronic Structures of VGen–/0 (n = 1–4) Clusters by Density Functional Theory and Multiconfigurational CASSCF/CASPT2 Method

Abstract: Density functional theory and the multiconfigurational CASSCF/CASPT2 method have been employed to study the low-lying states of VGe (n = 1-4) clusters. For VGe and VGe clusters, the relative energies and geometrical structures of the low-lying states are reported at the CASSCF/CASPT2 level. For the VGe and VGe clusters, the computational results show that due to the large contribution of the Hartree-Fock exact exchange, the hybrid B3LYP, B3PW91, and PBE0 functionals overestimate the energies of the high-spin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 45 publications
0
37
0
4
Order By: Relevance
“…The active space with 15 orbitals has been proven to be sufficient to study the lowlying states of VGe −/0 , VSi 3 -/0 , and VSi 4 -/0 clusters. [2,3,11] Also, most of the computer systems can handle CASSCF/CASPT2 calculations with a maximum of 15 orbitals in the active space.…”
Section: Methodsmentioning
confidence: 99%
“…The active space with 15 orbitals has been proven to be sufficient to study the lowlying states of VGe −/0 , VSi 3 -/0 , and VSi 4 -/0 clusters. [2,3,11] Also, most of the computer systems can handle CASSCF/CASPT2 calculations with a maximum of 15 orbitals in the active space.…”
Section: Methodsmentioning
confidence: 99%
“…However, the application of CASSCF/CASPT2 method is limited to very small systems because this method is computationally very expensive. The relative energies of the low‐lying states and the electron detachment energies of the anionic cluster as computed with the CASSCF/CASPT2 method prove to be sufficient to give assignments for the anion photoelectron spectroscopy . In the previous studies, all features in the photoelectron spectrum of VGe 3 − and VGe 4 − clusters were explained by the CASPT2 results.…”
Section: Introductionmentioning
confidence: 93%
“…The physical and chemical properties of transition metal‐doped germanium clusters are determined by their size, shape, and composition. In the literature, we can see a large amount of experimental and theoretical investigations on the structures of transition metal‐doped germanium clusters . It is found that doping of transition metal to pure germanium clusters can form stable cage structures that can be used as building blocks for synthesis novel materials …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations